PROSPECTS FOR APPLICATION OF FISCAL FEDERALISM FOREIGN MODELS IN THE CONDITIONS OF TRANSFORMATION CONOMY IN UKRAINE - Dluhopolskyy, Oleksandr (Journal of European Economy, 2017)
Basic concepts of fiscal federalism, principles and models of interbudget relations both in unitary, and in federal countries are analyzed. The urgency of this research is conditioned by availability of several administrative-territorial levels in each country, which are having specific relations in the area of money resources redistribution (that is similar to regional budgets either receiving grants or contributing to a central budget). The priority lines are suggested to intensify the budget independence of subnational governments from the view of present day international practice of fiscal federalism and interbudget transfers.